2021
DOI: 10.3390/ijerph18105239
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sitting Time, Screen Exposure and Physical Activity during COVID-19 Lockdown in South American Adults: A Cross-Sectional Study

Abstract: The worldwide prevalence of insufficient physical activity (PA) and prolonged sedentary behavior (SB) were high before the coronavirus (COVID-19) pandemic. Measures that were taken by governments (such as home confinement) to control the spread of COVID-19 may have affected levels of PA and SB. This cross-sectional study among South American adults during the first months of COVID-19 aims to (i) compare sitting time (ST), screen exposure, moderate PA (MPA), vigorous PA (VPA), and moderate-to-vigorous PA (MVPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
11
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
(46 reference statements)
6
11
1
3
Order By: Relevance
“…Studies from various countries have shown that during the COVID-19 pandemic physical activity (PA) decreased while sedentary behaviour increased. This was shown in various cross-sectional studies worldwide [4][5][6][7][8][9][10], and confirmed by several review articles [11,12]. Similar to international trends, studies from Austria have shown that during the COVID-19 pandemic, PA levels decreased by up to 48.9% [12,13].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Studies from various countries have shown that during the COVID-19 pandemic physical activity (PA) decreased while sedentary behaviour increased. This was shown in various cross-sectional studies worldwide [4][5][6][7][8][9][10], and confirmed by several review articles [11,12]. Similar to international trends, studies from Austria have shown that during the COVID-19 pandemic, PA levels decreased by up to 48.9% [12,13].…”
Section: Introductionsupporting
confidence: 58%
“…Beck Depression Inventory (BDI): Originally, the level of depression is categorized into four types using the validated German version of BDI [31]; no depression (scores 0-9), mild (10)(11)(12)(13)(14)(15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and severe depression (30-63) [32]. In our analysis individuals scoring between 10-63 points were described as exhibiting symptoms of depression.…”
mentioning
confidence: 99%
“…Globally, children and adolescents have increasingly adopted a more sedentary lifestyle, and they have become more occupied with digital devices in pace with the digital revolution during the last 30–40 years [ 1 ]. Additionally, the COVID-19 pandemic has, for many individuals, led to detriments in physical activity and a further increase in sedentary behaviour and use of near digital devices [ 2 , 3 ]. Sedentary behaviour increases from childhood to adulthood [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, multinational studies in the COVID-19 context, carried out in different latitudes worldwide including Latin America and Chile, report a negative impact of the pandemic on levels of physical activity and sedentary time, being related to a worse mental health in the adult population [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. These findings also apply to the university population.…”
Section: Introductionmentioning
confidence: 99%